Fragile fat masculinities: the narrative construction and masculine negotiation of fatphobia in Malayalam cinema - Raj, Sony Jalarajan; Gayathri, G. R.; Suresh, Adith K. (My University, 2025)
The portrayal of the male fat body in Indian cinema is intertwined with prevalent social constructs and gender stereotypes regarding idealized masculine corporeality. The fat character is frequently depicted as a source of humour that not only reinforces fatphobic attitudes but also underscores the normalization of body shaming in Indian society. This article scrutinizes the representations and discourses surrounding fatness within the context of Malayalam cinema, the South Indian film industry based in the state of Kerala. It specifically analyzes two key Malayalam films to understand how visual narratives construct fat bodies using humour to shed light on the protagonist’s struggles with body image, societal prejudices, and self-acceptance. This paper argues that the construction of fatphobia degrades male characters and reduces them to objects of revulsion, thereby reinforcing stereotypes of desirability and beauty. These films use a common narrative that presents fat characters as kind-hearted, childish and feminized to create a humanized body image to conceal the fatphobia that surrounds their masculinity. These forced narrative negotiations reinforce fragile fat masculinities through the exaggerated social performance of fatness as something that invites a pleasurable gaze without destigmatizing the insecurities and societal norms around body image and masculinity.
Keywords: fatphobia; fat studies; masculinity studies; Indian cinemas; Malayalam cinema